Socio-Economic Implications of Land Conflicts on the Livelihood of Communities in Dodoma City, Tanzania - Adwell, Magdalena Mwaruanda; Kaburire, Laurent (International Journal of Conflict Management, 2025)
Purpose: The study assessed land conflicts and their socio-economic implications on communities living in the Dodoma City Council, whereby Nzuguni Ward was selected as a case study. Methodology: The study used a mixed method, which accommodated a case study research design. Structured questionnaires and interviews were used to collect data involving a total of 98 respondents randomly selected from the study area. Quantitative data were analysed using descriptive analysis, while qualitative data were analysed using the content analysis method. Findings: The study revealed that land conflicts have resulted in various socio-economic implications, such as loss of property, forced relocation, reduced income opportunities, and increased household poverty among the victims in the study area. Unique Contribution to Theory, Policy and Practice: There is a need for policy interventions to address the loss of property, forced relocations and increased poverty connected to land conflicts. Furthermore, the study recommends for strict anti-corruption measures, improved land tenure security, community empowerment, and policy reforms to mitigate land conflicts. Focusing on the Conflict Theory, the findings provide evidence that powerful actors persistently expropriate resources from vulnerable individuals, thereby intensifying the social and economic implications. Regarding the Institutional Theory, the findings demonstrate that institutions entrusted with the protection of property rights have only partially addressed land conflicts. By addressing these challenges, stakeholders can promote sustainable land management and socio-economic stability in peri-urban areas like Nzuguni.